Epoch Synchronous Overlap Add (ESOLA) A Concatenative Synthesis Procedure for Speech - Datta, Asoke Kumar (Signals and Communication Technology, 2018)
This book presents details of a text-to-speech synthesis procedure using epoch synchronous overlap add (ESOLA), and provides a solution for development of a text-to-speech system using minimum data resources compared to existing solutions. It also examines most natural speech signals including random perturbation in synthesis. The book is intended for students, researchers and industrial practitioners in the field of text-to-speech synthesis. .